Automatic Control System Design of the Threshing Station Model, Case Study in PT. Perkebunan Nusantara V-PKS Sei Galuh - Hamzah, Amir; Arief, Dodi Sofyan; Sihombing, Galuh Leonardo; Andri, Andri (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2017)
This paper presents a design for the automatic control system of the threshing station model using PLC Zelio smart relay. Threshing station is a station where a process of separation palm kernel from the bunch by way of slamming into a rotating drum. The threshing station model is a shape which resembles of the threshing station palm oil mill of PT. Perkebunan Nusantara V- PKS Sei Galuh, it has been scaled 1:8. PLC (Programmable Logic Controller) is a microprocessor based on instrument that can be programmed to control the machining process automatically. This system design has 2 inputs and 3 outputs. The inputs are push button to turn on and turn off of the works system and a rotary encoder sensor to detect rotating screw conveyor. The outputs are 3 units of DC motors. The programming language is used the ladder diagram by using the Software Zelio Soft 2. This system includes design of ladder diagram program, design of control system on auto feeder and design of rotary encoder sensor. The result of this design is revealed that auto feeder runs automatically turn on for 60 seconds and turn off for 30 seconds, continuously. The sensor works with voltage is 4.4 Volt at the moment un-stunted and 0.1 Volt when the stunted.